Possible impacts on the subjective quality of life of children after divorce/separation of parents in the Czech Republic - Witzanyová, Aneta; Nesnídal, Rostislav; Velemínský, Miloš; Baloun, Ingrid (Journal of Nursing, Social Studies and Public Health, 2021)
Introduction: Divorce and separation of parents have a significant impact on the quality of life of children. The experience and psychological development of these children are often affected by parental disputes, which also results in changes in their quality of life. Goal: This research aims to show what impact a divorce/separation of parents can have on children's subjective quality of life, including the effects on the psyche, and the realization of the child's right to both parents in the Czech Republic. Methods: The research was carried out by qualitative document analysis, specifically the grounded theory technique. Ten families who needed an expert opinion for a childcare agreement underwent a thorough qualitative analysis of file documentation. The obtained information was subjected to coding, and the main result established grounded claims. Results and discussion: The main benefit of the research is that it shows the most significant problems are caused by parents' efforts to reduce access rights or win disputes over childcare. Often, parents do not hesitate to use various forms of behaviour that are ultimately the most hurtful for children. These threaten the successful mental development of the children and decrease the subjective quality of life. The ideal way to rectify the relationship is to try to reach an agreement, which can make it easier and fairer for both parents, with the help of mediation and psychological counselling. Conclusions: The analysis and interpretation of the obtained data revealed that the divorce/separation of the parents is stressful for children. Still, the most significant problems are caused by the efforts of the parents to win disputes concerning the care of the children by various means. However, this kind of behaviour is ultimately the most hurtful for children and threatens their successful mental development.
Keywords: Divorce; Family Relations; Counseling; rozvod; Česká republika; Humans; kvalita života; adaptace psychologická; duševní zdraví; lidé; Child; dítě; Mental Health; Czech Republic; Adaptation, Psychological; Quality of Life; rodinné vztahy; poradenství